Statutory discounts as a barrier to the integration of bus and rail transport - Karol Wach (Przegląd Komunikacyjny)
Abstract: The subject of the article is the issue of statutory concessions applied in public collective transport. The level of their differentiation in relation to bus and rail transport is a serious barrier to the tariff integration of these two means of transport. Hence, in the course of works on the amendment to the act on public collective transport, it seems advisable to attempt to standardize statutory concessions, as well as to include provisions relating to them to the indicated normative act. In the current legal state, the provisions regulating this issue have been included in at least a few acts. The adoption of the assumption assuming their unification should lead to simplification of the currently applicable system, and thus accelerate the process of ticket integration. Keywords: Tariff integration; Ticket; Statutory discount